2016
DOI: 10.1111/pai.12565
|View full text |Cite
|
Sign up to set email alerts
|

Non‐immediate hypersensitivity reactions to beta‐lactam antibiotics in children – our 10‐year experience in allergy work‐up

Abstract: A diagnostic work-up should be performed in all children with non-immediate reactions to BL, to remove a false label of hypersensitivity. Even though only 57 (5.5%) of 1026 children displayed positive responses to delayed-reading intradermal tests to BL, such tests appear to be useful in order to reduce the risk for positive DPTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 34 publications
8
89
3
1
Order By: Relevance
“…North America versus Europe) 100103 . It is important to note that the sensitivity of testing methods varies for the approach, the underlying clinical phenotype and the implicated drug.…”
Section: Cross-reactivity and Cross-checking: The Importance Of Side Chmentioning
confidence: 99%
“…North America versus Europe) 100103 . It is important to note that the sensitivity of testing methods varies for the approach, the underlying clinical phenotype and the implicated drug.…”
Section: Cross-reactivity and Cross-checking: The Importance Of Side Chmentioning
confidence: 99%
“…In recent years, a number of papers have challenged the academic guidelines and have explored the feasibility of performing OPT without skin tests in children with suspicion of a benign non‐immediate reaction . In spite of reported good results, economic savings, and observed satisfaction by parents and doctors, this attitude is still debated and some authors still consider performing intradermal tests, mainly due to fear of severe reactions during OPT . As a result, in current clinical practice, things are not so clear and very different approaches are followed by practicing clinicians…”
Section: What To Do With a Child With Suspected Blh In A Specialized mentioning
confidence: 99%
“…The risk of death due to anaphylactic shock after oral administration of amoxicillin in the general population is extremely low . Under controlled conditions, positive OPT have usually been mild in children with a history of non‐severe cutaneous reactions, or even in children with a history of anaphylactic reactions and negative skin tests, and severe reactions are very uncommon and easily treated . On the other hand, OPT have been very rarely performed on children (and adults) with positive skin tests or with a history of severe delayed cutaneous‐systemic reactions (Stevens‐Johnson syndrome, toxic epidermal necrolysis, acute generalized exanthematous pustulosis, DRESS syndrome…), in accordance with precautions and contraindications reaffirmed in the last International Consensus on drug allergy …”
Section: Safety Of Opt For Suspected Blhmentioning
confidence: 99%
“…It has been suggested that intercurrent viral infections at the time of an initial exposure may augment a drug reaction. On re-exposure to the drug once well, many children may not develop a subsequent reaction giving rise to false negative results 9 19. The European Network for Drug Allergy (ENDA) advocates the use of patch tests, delayed-reading intradermal test (IDT) and lymphocyte transformation test (LTT) followed by a long-term oral challenge test (OCT) when testing for NIRs in paediatric patients 20–23.…”
Section: Commentarymentioning
confidence: 99%